EFEKTIVITAS EKSTRAK TANAMAN HUTAN RAWA SEBAGAI BIOINSEKTISIDA DALAM MENGENDALIKAN Spodoptera litura F. PADA SKALA LABORATORIUM - Syaiful Asikin; Muhammad Helmy Abdillah (EnviroScienteae, 2022)
To overcome the emergence of environmental pollution due to the control of pests and plant diseases from the use of chemical pesticides, preventive measures are needed by exploring the potential of endemic and non-endemic plants as the main ingredients for making organic insecticides. The purpose of this study was to determine the effectiveness of extracts from plant materials from Tanjung, Belimbing Wuluh, Jingah, Jelatang, Gambir, Ketapang, Kemang, and Pulai to be used as the main ingredients of insecticides to control the mortality of armyworm (Spodoptera litura F.) in vivo in the laboratory of Balai Penelitian Lahan Rawa. To obtain the purpose of this study, the data were analyzed by means of variance to determine the significance of the value of the treatment, if there were at least two pairs of different treatments, then it was continued with the mean difference test using the BNJ 5% model. The results showed that the 8 types of swamp plant extracts were effective in controlling armyworm pests because their mortality was above 60% in a period of ≤ 48 hours. The highest pest mortality occurred in the application of feed with Pulai plant extract, which was around 84.0% after 60 hours of application.